The sources of modern linguistics terminological apparatus - Shuiskaya Yu.V., Myltseva M. V., Arustamyan D.V., Gurtskaya S.B., Drozdova E.A., (Opción, 2019)
In the paper by optionalitywe mean a speech modification functioning in the language, manifested in a peculiar deviation within the norm, which exists alongside with the codified literary obligatory variant in certain linguistic and extralinguistic conditions. The functional-dynamic method is one of the main methods we used in here. For the analysis of faculty, an attempt is made to use the studied parameters of such a linguistic phenomenon as variance. Thus, we suppose that the phenomenon of optionality is basically associated with the processes of changes in linguistic systems and is a factor in the dynamics of linguistic development.